2021
DOI: 10.21037/jtd-2019-ipicu-16
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic bronchoscopy facilitates liberation from mechanical ventilation and improves quality of life for critically ill patients with central airway obstruction

Abstract: Central airway obstruction (CAO) remains a challenging disease for both patients who are suffering from it and for physicians who are managing it. Patients will frequently present with acute symptoms of respiratory failure that require management in an intensive care unit (ICU). While the true prevalence and incidence of CAO in the ICU setting is unknown, recent estimates suggest that approximately 20-30% of patients with a cancer diagnosis may present with CAO or develop it after diagnosis. Therapeutic bronch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…In such situations, the feasibility of airway stenting under moderate sedation should be considered. It is important to mention, however, that although therapeutic bronchoscopy and airway stenting may pose procedure-related risks, they have also been shown to significantly improve symptoms, and even liberate critically ill patients from invasive mechanical ventilation [26,27]. In fact, Ost et al [8] identified that higher-risk patients (those with the highest pre-procedural report of dyspnea and the lowest pre-procedural functional status) had the greatest improvement after therapeutic bronchoscopy for malignant CAO.…”
Section: General Principles In Patient Selectionmentioning
confidence: 99%
“…In such situations, the feasibility of airway stenting under moderate sedation should be considered. It is important to mention, however, that although therapeutic bronchoscopy and airway stenting may pose procedure-related risks, they have also been shown to significantly improve symptoms, and even liberate critically ill patients from invasive mechanical ventilation [26,27]. In fact, Ost et al [8] identified that higher-risk patients (those with the highest pre-procedural report of dyspnea and the lowest pre-procedural functional status) had the greatest improvement after therapeutic bronchoscopy for malignant CAO.…”
Section: General Principles In Patient Selectionmentioning
confidence: 99%
“…Many aspects of care modify the relationship between tracheostomy tubes and patient outcomes. At the intersection of interventional pulmonology and critical care is therapeutic bronchoscopy, which can improve pulmonary hygiene, facilitating liberation from the ventilator and improving quality of life ( 30 , 31 ). Effective care requires partnership across all professionals participating in tracheostomy care, and the GTC scaffolds quality improvement efforts on a global scale across institutions, allowing for benchmarking of outcomes.…”
Section: High Reliability Tracheostomy Carementioning
confidence: 99%